Estudo da influência do agregado graúdo de diferentes origens mineralógicas nas propriedades mecânicas do concreto - Miguel Fernando Schettini Alhadas (2008)
The goal of this study is to present the effects of the different types of coarse aggregate on the mechanical properties of concrete: compressive strength and secant modulus of elasticity (MOE). Limestone, gneiss, dolomite and basalt were used as coarse aggregates. These aggregates came from six different regions in the state of Minas Gerais. ABNT type CP III RS cement and natural sand, as fine aggregate, were employed in the fabrication of the concrete. The concrete mix proportion was based on environmental class II of NBR 6118: minimum characteristic compressive strength equal to 25 MPa and water cement ratio 0.60. The mechanical properties were evaluated 3, 7, 14, 21 and 28 days after casting the concrete. The test results indicate expressively the better performance of the concretes fabricated with dolomite and basalt aggregates. Good correlation was achieved between the measured MOE values for the different concretes with the values calculated employing expressions in terms of the compressive strength suggested by NBR 6118, ACI 318, EUROCODE 2 and CEB 1990.